Hukum dan Keadilan Sosial dalam Perspektif Hukum Ketatanegaraan - Ahmad Fadlil Sumadi (Jurnal Konstitusi, 2015)
Law in this discussion is the law that is deliberately formed (by designed) by  the state, not the law that occurs naturally in the society, which constitute the crystallization of human interaction within the society as the subject of law.  Law is known as the common law or customary law and the second is the religious law, in particular, Islam with its Islamic law. The process of formation of common law or customary law is from the bottom upward (bottom-up process) while the establishment of islamic law is from top to bottom (top-down). The same as the nature of the process of formation of Islamic law is the in question in this discussion, which is the law called state legislation, or which is also usually known as laws and regulations. The only difference is, Islamic law is made by God, Allah SWT,  while the maker of statutory laws is a state institution of which the major function is to make laws (legislative power). Legislation is interrelated to with humanity and justice, both in the establishment, implementation, and enforcement. This can be proven by tracing since the establishment of the state, particularly Indonesia, because the law is one of the implementation of state functions. State is established on the basis of motivation associated with humanity and justice, so that the objectives and the foundations are also related to humanity and justice. The State and the law is  an instrument of humanity and justice, therefore, state and law must be related to humanity and justice, and thus, also would not be enough in the instrumental perspective, the state and the law itself without humanity and justice in serving the society.